2019
DOI: 10.1590/1413-81232018245.04432019
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to access to palliative care services perceived by gastric cancer patients, their caregivers and physicians in Santander, Colombia

Abstract: Gastric cancer (GC) is a public health issue with high incidence and mortality in Colombia due to tardy diagnosis and barriers to access to curative treatment; this leaves palliative care (PC) as the only option. Our aim is to describe the access barriers to PC perceived by adults with GC, caregivers and physician in Santander, Colombia. A qualitative study was carried out with the analysis of the grounded theory (Strauss and Corbin), through semi-structured interviews, after sampling for convenience we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 22 publications
0
22
0
16
Order By: Relevance
“…The 29 studies identified included 8 quantitative studies, [25][26][27][28][29][30][31][32] 18 qualitative studies, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and 3 mixed-methods studies. [52][53][54] The sample size ranged from 10 participants to 313 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 29 studies identified included 8 quantitative studies, [25][26][27][28][29][30][31][32] 18 qualitative studies, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and 3 mixed-methods studies. [52][53][54] The sample size ranged from 10 participants to 313 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies examined the barriers to PC utilization related to persons with cancer and their family. 29,30,35,40,42,49,50 The most common patient-related barriers included negative images/ stereotyping of PC, denial of the terminal nature of the disease/unrealistic expectations, and economic/logistic barriers. These are discussed below.…”
Section: Barriers Related To the Patient And The Familymentioning
confidence: 99%
See 2 more Smart Citations
“…As of 2014, Colombia has organised legislation regarding the availability of palliative care with the aim of guaranteeing access to palliative care to all patients who may benefit from such care, including those with cancer and non-cancer diseases [ 21 ]. Nevertheless, the offer of palliative care services in the country is still scarce and mainly limited to hospital-based settings and centralised in large cities [ 22 , 23 , 24 , 25 ], despite the fact that throughout the country, there was an increase in palliative care services from 23 in 2013 to 79 in 2020. This increase in service provision is still insufficient for the needs of the population [ 26 ], whereas the global atlas of palliative care outlined Colombia [ 27 ] as having generalised palliative care provision [ 28 ].…”
mentioning
confidence: 99%